Mode choice modeling of electric air taxis for long-distance airport trips - Atul Subedi; Patrick A. Singleton (Transportation Research Interdisciplinary Perspectives)
As congestion and environmental concerns grow, innovative solutions like electric air taxis (EATs) are gaining attention as efficient and sustainable options for improving airport trips. To understand preferences for EATs for long-distance airport access/egress trips, we conducted a stated choice experiment and estimated integrated choice and latent variable (ICLV) models. The study analyzed choices among EAT, private vehicle (PV), public transport (PT), and transportation network companies (TNC), collecting data in 2024 from 1028 US adults traveling 75–200 miles one-way to/from airports. In-vehicle travel time, travel cost, and access time for all modes showed significant negative associations with mode choice, with access time being particularly critical for EAT. A decrease in service frequency of EAT significantly reduced its selection odds, and autonomy in travel modes was found to present a disutility, with the most substantial negative impact on EAT. Perceived ease of use was highest for EAT, while perceived trust was highest for PT. Travelers were more inclined to choose EAT when it is perceived as dependable and reliable. Including luggage costs in the total travel cost for EAT significantly increased preferences compared to scenarios with extra fees. Based on our findings, the highest value of travel time savings (VTTS) was for EAT at $46.09/hr, followed by PV at $38.63/hr, PT at $37.81/hr, and TNCs at $30.40/hr. EAT’s access time VTTS was highest, at $53.46/hr. These findings provide valuable insights for airlines, airport operators, EAT companies, and policymakers regarding the market potential of EATs for long-distance airport trips.